KELUARGA SEBAGAI BASIS UTAMA PELAKSANAAN PENDIDIKAN KARAKTER BAGI ANAK - Sjeny Liza Souisa (IAKN Ambon, 2020)
The Covid 19 pandemic which has temporarily hit human life not only has a negative impact in the field of education, but also has a positive impact, where families are given large space and time to return to playing their duties and responsibilities as the main basis of education for children including carrying out character education. Character education models that can be carried out by families, in this case parents and adults for children, include worshiping together, loving and guiding, admonishing when children make mistakes, habituation and modeling. So that parents can do their role well as educators, parents need to be nurtured and trained to have good and correct knowledge and skills about character education. Therefore, it takes cooperation that always exists between parents, school and church.